Photoactivatable Dopamine and Sulpiride to Explore the Function of Dopaminergic Neurons and Circuits - Asad, Naeem (ACS Chem Neurosci, 2020)
[Image: see text] Kinetic analysis of dopamine receptor activation and inactivation and the study of dopamine-dependent signaling requires precise simulation of the presynaptic release of the neurotransmitter dopamine and tight temporal control over the release of dopamine receptor antagonists. The 8-cyano-7-hydroxyquinolinyl (CyHQ) photoremovable protecting group was conjugated to dopamine and the dopamine receptor antagonist sulpiride to generate “caged” versions of these neuromodulators (CyHQ-O-DA and CyHQ-sulpiride, respectively) that could release their payloads with 365 or 405 nm light or through 2-photon excitation (2PE) at 740 nm. These compounds are stable under physiological conditions in the dark, yet photolyze rapidly and cleanly to yield dopamine or sulpiride and the caging remnant CyHQ–OH. CyHQ-O-DA mediated the light activation of dopamine-1 (D1) receptors on the breast cancer cell line MDA-MB-231 in culture. In mouse brain slice from the substantia nigra pars compacta, localized flash photolysis of CyHQ-O-DA accurately mimicked the natural presynaptic release of dopamine and activation of dopamine-2 (D2) receptors, causing a robust, concentration-dependent, and repeatable G protein-coupled inwardly rectifying potassium channel-mediated outward current in whole-cell voltage clamp recordings that was amplified by cocaine and blocked by sulpiride. Photolysis of CyHQ-sulpiride rapidly blocked synaptic activity, enabling measurement of the unbinding rates of dopamine and quinpirole, a D2 receptor agonist. These tools will enable more detailed study of dopamine receptors, their interactions with other GPCRs, and the physiology of dopamine signaling in the brain.